SPECISMO: STORIA (FILOSOFICA) DI UN NEOLOGISMO (Rassegna di Diritto, Legislazione e Medicina Legale Veterinaria, 2019)
The term "speciesism" has become in common use, both in current language and in the literature for the protection of animals. However, with a careful analysis of the variety of definitions offered in many dictionaries and encyclopedias of the sector, it emerges that its meaning is not always univocal. This neologism thus appears to be both indispensable and ambiguous. To make it clearer, I propose to study its genesis and historical development. The word speciesism was invented by the psychologist Thomas Ryder in the early Seventies of the last century, in the context of the Oxford Group and was later philosophically accredited by Peter Singer. Its value varies from being a psychological expedient useful to ask questions about the opportunity to protect animals, to indicate a prejudice or discrimination towards animals that have to be overcome, to propose an animalistic ethics of utilitarian matrix and consequentialist based on a questionable interpretation of Bentham that insists on the evaluation of pain at the expense of the role of compassion. I will conclude by showing how speciesism has had a determining historical role, but today it is no longer the only strategy to protect animals, nor the most convincing, also in light the of recent legislation.